A Study of N, N-Diethylammonium O, O′-Di(p-methoxyphenyl)dithiophosphate as New Corrosion Inhibitor for Carbon Steel in Hydrochloric Acid Solution. (18th February 2016) - Lai, Chuan; Xie, Bin; Liu, Changlu; Gou, Wan; Zhou, Lvshan; Su, Xiulan; Zou, Like
Abstract : N, N-Diethylammonium O, O′-di( p -methoxyphenyl)dithiophosphate (EAPP) as a new corrosion inhibitor was synthesized in the present work. The corrosion inhibition of EAPP in hydrochloric acid for carbon steel was evaluated by potentiodynamic polarization measurements, electrochemical impedance spectroscopy, weight loss measurements, and scanning electron microscopy. The results indicate that the EAPP is mixed type inhibitor, and the adsorption of EAPP on carbon steel surface obeys Langmuir isotherm. In addition, the inhibition efficiency increases with increasing the concentration of inhibitor and decreases with increasing the hydrochloric acid concentration, temperature, and storage time.